Assessment of cardiopulmonary resuscitation equipment in resuscitation trolleys in district hospitals in Botswana: A cross-sectional study - Billy M. Tsima; Lakshmi Rajeswaran; Megan Cox (AOSIS, 2019)
Introduction: Successful cardiopulmonary resuscitation (CPR) relies, in part, on the availability and the correct functioning of resuscitation equipment. These data are often lacking in resource-constrained African settings. Aim: To assess the availability and the functional status of CPR equipment in resuscitation trolleys at district hospitals in Botswana. Setting: The study was conducted across four district hospitals in Botswana. Methods: A cross-sectional study was conducted using a checklist adopted following the Emergency Medical Services of South Africa (EMSSA) guidelines, modified and contextualised to Botswana. Results: All the four district hospitals had inadequate number of CPR equipment available in the resuscitation trolleys. The overall availability of drugs and equipment ranged from 19% to 31.1%. Availability of equipment needed for maintaining circulation and fluids ranged from 27% to 49%, while availability of items for airway and breathing ranged from 9.2% to 24.1%. The overall availability of essential drugs for resuscitation was only 20.4%, and in some wards expired drugs were kept in the trolley. Out of 40 wards that participated in the study, only 10 kept CPR algorithms in the resuscitation trolley. The resuscitation trolley was checked on a daily basis only in the critical care units. Conclusion: The resuscitation trolleys were not maintained as per standards. Failure to improve the existing situation could negatively impact the outcome of CPR. Evidence-based standard checklists for resuscitation trolleys need to be enforced to improve the quality of CPR provision in district hospitals in Botswana.